Perbandingan Proses Esterifikasi dan Esterifikasi -Trans-esterifikasi dalam Pembuatan Biodisel dari Minyak Jelantah - Niken Pratiwi; Masriani Masriani; Indah Prihatiningtyas (Seminar Nasional Teknik Kimia Kejuangan, 2016)
In recent years, some researchers are exploring many new sources of energy, such as biofuels. Biodiesel attracted the attention of various researchers as an alternative fuel because it is non-toxic, biodegradable and renewable as well as contributing the minimum amount of net greenhouse gases, such as CO2, SO2 and NO emissions into the atmosphere. The use of waste cooking oil to produce biodiesel reduced the raw material cost. The acid-catalyzed process using waste cooking oil proved to be technically feasible with less complexity than the alkali-catalyzed process using waste cooking oil, thereby making it a competitive alternative to commercial biodiesel production by the alkali-catalyzed process. The main objective of this study was to compare the process of making biodiesel. Esterification process would be compared with esterification followed by a trans-esterification process. The results showed that biodiesel was produced by esterification followed by trans-esterification process and esterification process , they have met SNI for parameters such as density, acid number, pH, cloud point and flash point, but the parameters of the viscosity and water content did not meet standards. Biodiesel using esterification followed by trans-esterification) was better than esterification process due to the yield produced higher (62.667%) than the esterification process (48%)